Effects and mechanism of Aβ1−42 on EV-A71 replication - Zhong, Ming; Wang, Huiqiang; Yan, Haiyan; Wu, Shuo; Wang, Kun; Yang, Lu; Cui, Boming; Wu, Mengyuan; Li, Yuhuan (Virology journal, 2022)
Background β-Amyloid (Aβ) protein is a pivotal pathogenetic factor in Alzheimer’s disease (AD). However, increasing evidence suggests that the brain has to continuously produce excessive Aβ to efficaciously prevent pathogenic micro-organism infections, which induces and accelerates the disease process of AD. Meanwhile, Aβ exhibits activity against herpes simplex virus type 1 (HSV-1) and influenza A virus (IAV) replication, but not against other neurotropic viruses. Enterovirus A71 (EV-A71) is the most important neurotropic enterovirus in the post-polio era. Given the limitation of existing research on the relationship between Aβ and other virus infections, this study aimed to investigate the potent activity of Aβ on EV-A71 infection and extended the potential function of Aβ in other unenveloped viruses may be linked to Alzheimer's disease or infectious neurological diseases. Methods Aβ peptides 1–42 are a major pathological factor of senile plaques in Alzheimer’s disease (AD). Thus, we utilized Aβ1–42 as a test subject to perform our study. The production of monomer Aβ1–42 and their high-molecular oligomer accumulations in neural cells were detected by immunofluorescence assay, ELISA, or Western blot assay. The inhibitory activity of Aβ1–42 peptides against EV-A71 in vitro was detected by Western blot analysis or qRT-PCR. The mechanism of Aβ1–42 against EV-A71 replication was analyzed by time-of-addition assay, attachment inhibition assay, pre-attachment inhibition analysis, viral-penetration inhibition assay, TEM analysis of virus agglutination, and pull-down assay. Results We found that EV-A71 infection induced Aβ production and accumulation in SH-SY5Y cells. We also revealed for the first time that Aβ1–42 efficiently inhibited the RNA level of EV-A71 VP1, and the protein levels of VP1, VP2, and nonstructural protein 3AB in SH-SY5Y, Vero, and human rhabdomyosarcoma (RD) cells. Mechanistically, we demonstrated that Aβ1–42 primarily targeted the early stage of EV-A71 entry to inhibit virus replication by binding virus capsid protein VP1 or scavenger receptor class B member 2. Moreover, Aβ1–42 formed non-enveloped EV-A71 particle aggregates within a certain period and bound to the capsid protein VP1, which partially caused Aβ1–42 to prevent viruses from infecting cells. Conclusions Our findings unveiled that Aβ1–42 effectively inhibited nonenveloped EV-A71 by targeting the early phase of an EV-A71 life cycle, thereby extending the potential function of Aβ in other non-envelope viruses linked to infectious neurological diseases.